2022
DOI: 10.1007/s12298-022-01172-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering in food crops to enhance ascorbic acid production: crop biofortification perspectives for human health

Abstract: Ascorbic acid (AsA) also known as vitamin C is considered as an essential micronutrient in the diet of humans. The human body is unable to synthesize AsA, thus solely dependent on exogenous sources to accomplish the nutritional requirement. AsA plays a crucial role in different physiological aspects of human health like bone formation, iron absorption, maintenance and development of connective tissues, conversion of cholesterol to bile acid and production of serotonin. It carries antioxidant properties and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 108 publications
(137 reference statements)
3
11
0
Order By: Relevance
“…In earlier works, growth rate has been associated with AsA, based on external applications leading to accelerated growth [ 29 ]. In transgenic studies, overexpression of AsA biosynthetic enzymes and related regulators provided evidence for the growth-promoting and stress-ameliorative effects of AsA [ 30 ]. Therefore, AsA levels were measured in leaf tissues of both hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier works, growth rate has been associated with AsA, based on external applications leading to accelerated growth [ 29 ]. In transgenic studies, overexpression of AsA biosynthetic enzymes and related regulators provided evidence for the growth-promoting and stress-ameliorative effects of AsA [ 30 ]. Therefore, AsA levels were measured in leaf tissues of both hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genes of the l -galactose/ d -mannose pathways have resulted in diverse crops to increase ascorbic acid content, but the results were not satisfactory [ 141 , 142 ]. It has been shown that the countenance of GGP, which characterizes the blockage of ascorbic acid biosynthesis [ 143 ], is a beautiful approach to biofortify vitamin C [ 144 ]. For example, in Arabidopsi s, transient overexpression of the GGP gene results in an increase in ascorbic acid content up to 2.5 times, however; increased expression of the extra genes implicated in the same biosynthetic pathway does not result in significant changes in ascorbic acid content [ 145 ].…”
Section: Nutrients Used In Biofortificationmentioning
confidence: 99%
“…Among the easily decomposable organics, tetracycline (TC) could be easily degraded by most microorganisms, but the residue can lead to selective variation of microorganisms and the emergence of drug-resistant pathogens [7][8][9]. As a reducing agent, ascorbic acid (AA) is widely used in medicine, food and cosmetics [10]. However, excessive intake would disrupt the normal metabolism of cells, leading to coronary heart disease and urinary calculi [11][12].…”
Section: Introductionmentioning
confidence: 99%